Existence of bounded solutions of Neumann problem for a nonlinear degenerate elliptic equation - Salvatore Bonafede (Electronic Journal of Differential Equations, 2017)
We prove the existence of bounded solutions of Neumann problem for nonlinear degenerate elliptic equations of second order in divergence form. We also study some properties as the Phragmen-Lindelof property and the asymptotic behavior of the solutions of Dirichlet problem associated to our equation in an unbounded domain.